A 3D-gis extensionf for sky view factors assessment in urban environment - Souza, Léa Cristina Lucas (2003)
This paper presents a Geographic Information System (GIS) 3D extension that is a tool to simulate the representation of sky view factors (SVF) while calculating their values. The sky view factor (SVF) is a climatological parameter used to characterize radiation properties on urban areas and to express the relationship between the visible area of the sky and the portion of the sky covered by buildings viewed from a specific point of observation. The implementation of this tool in a 3D GIS is useful not only because it allows straight and quick urban geometry analysis from several points of observation, but also because it can help to predict sky view factors due to future buildings without the usual associated costs of cameras and image processing. The algorithm was developed by applying the software ArcView GIS1 and its 3D Analyst extension, allowing an automatic delineation of the visible sky and obstructions.